2015
DOI: 10.6002/ect.mesot2014.p177
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic Complications After Liver Transplant: Experience at a Single Center

Abstract: Objectives: Neurologic complications occur frequently after liver transplants. Up to 43% of patients experience severe postsurgical neurologic complications. These complications are significantly associated with longer hospital stay, morbidity, and mortality. The aim of this retrospective study was to evaluate the type and incidence of neurologic complications after liver transplants in adult patients. Materials and Methods:We retrospectively evaluated the medical records of 176 adult patients who had undergon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 21 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…1 Derle and colleagues found a prevalence of peripheral neuropathy of 1.7% after liver transplant. 6 We found a neuropathic pain prevalence of 6.2%. This was brought about by a greater number of patients with diabetes and the longer follow-up (as long as 8 years among transplant recipients).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…1 Derle and colleagues found a prevalence of peripheral neuropathy of 1.7% after liver transplant. 6 We found a neuropathic pain prevalence of 6.2%. This was brought about by a greater number of patients with diabetes and the longer follow-up (as long as 8 years among transplant recipients).…”
Section: Discussionmentioning
confidence: 80%
“…[1][2][3][4][5][6] Ramos and associates reported a neuropathic pain prevalence of 1.4% among 140 solid-organ transplant recipients. 1 Derle and colleagues found a prevalence of peripheral neuropathy of 1.7% after liver transplant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been a decreasing trend in the incidence of this type of seizure, which may be due to timely postoperative managements that include correcting metabolic disorders, dealing with poisoning and using immunosuppressive agents with fewer side effects [52]. [53] conducted a survey of 176 patients who had received liver transplants between 1955 and 2013 and found that approximately 6% of the adult patients had seizures. Only two of the patients showed SE or focal awareness impaired seizure, and the others were characterized as GTCSs.…”
Section: Etiology and Risk Factorsmentioning
confidence: 99%
“…Wszolek et al [51] found that there are two peaks of seizure occurrence after transplantation, namely, the first week and the fifth to sixteenth weeks after surgery. Adult patients usually experience seizures in the early postoperative period [51,[53][54][55][56]. Xie et al [54] found that pediatric patients often show seizures within the first two weeks after liver transplantation; this idea was supported by Kılıç et al [55].…”
Section: Onset Time and Course Of Diseasementioning
confidence: 99%